Beast of stone - Park, Linda Sue (Park, Linda Sue. Wing & claw, 2019)
Raffia and his ability to unleash the magical ability of plants have failed to free the animals captured by the Chancellor. Now Raffa and his allies must face the Chancellor's armies in battle and Raffa wants to prevent injuries and worse on both sides since the Chancellor's creatures are fighting against their will. He must use his skills as an apothecary to bring a resolution to an unfair battle.